Repurposing the Antiemetic Metoclopramide as an Antiviral Against Dengue Virus Infection in Neuronal Cells - Shen, Ting-Jing; Hanh, Vu Thi; Nguyen, Thai Quoc; Jhan, Ming-Kai; Ho, Min-Ru; Lin, Chiou-Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Dengue virus (DENV) is transmitted by Aedes mosquitoes to humans and is a threat worldwide. No effective new drugs have been used for anti-dengue treatment, and repurposing drugs is an alternative approach to treat this condition. Dopamine 2 receptor (D2R) is a host receptor positively associated with DENV infection. Metoclopramide (MCP), a D2R antagonist clinically used to control vomiting and nausea in patients with DENV infection, was putatively examined for inhibition of DENV infection by targeting D2R. In the mouse neural cell line Neuro-2a with D2R expression, a plaque assay demonstrated the antiviral efficacy of MCP treatment. However, in the cell line BHK-21, which did not express D2R, MCP treatment caused no further inhibition of DENV infection. Either MCP treatment or exogenous administration of a neutralizing D2R antibody blocked DENV binding. Treatment with MCP also reduced DENV dsRNA replication and DENV-induced neuronal cell cytotoxicity in vitro. An in vivo study demonstrated the antiviral effect of MCP against DENV-induced CNS neuropathy and mortality. These results showed that repurposing the D2R-targeting antiemetic MCP is a potential therapeutic strategy against DENV infection.